The Influence of Communication Patterns and Physiological Conditions on Temper Tantrum Behavior in Early Childhood in Timbangan Village, Ogan Ilir Regency - Estia Ningsih; Mega Nurrizalia; Evy Ratna Kartika Waty (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Research on tantrum behavior in early childhood has been conducted to determine the influence of communication patterns and physiological conditions on the occurrence of temper tantrum behavior in children aged 4-6 years in Timbangan Village, Ogan Ilir Regency. This study uses a quantitative approach with a correlational design. Data analysis was performed through t-test, f-test, coefficient of determination, and multiple linear regression calculations. Data were collected through questionnaires and observation activities. The results of this study show a t-value of -2.056 with a significance of 0.043, indicating a significant influence of communication patterns on the occurrence of temper tantrum behavior in children aged 4-6 years in Timbangan Village, with an influence percentage of 5.42%. Furthermore, the t-value of 7.678 with a significance of 0.000 means that there is a significant influence of physiological conditions on the occurrence of temper tantrum behavior in children aged 4-6 years in Timbangan Village, with an influence percentage of 44.86%. The findings suggest that if the communication pattern between parents and children is better or more functional, the likelihood of temper tantrum behavior occurring in children will decrease, and vice versa. On the other hand, if physiological conditions such as fatigue, hunger, and illness in children increase, the likelihood of temper tantrum behavior also increases, and vice versa. The influence of communication patterns and physiological conditions on temper tantrum behavior in early childhood (4-6 years) in this study is expected to provide the best education in addressing tantrums in children in society for various parties, such as parents, educators, teachers, relevant institutions (early childhood education institutions, women's organizations, counseling and socialization agencies, health institutions), and others.